Retirement: Does individual unemployment matter? Evidence from Danish panel data 1980 - 2009 - Trine Filges; Mona Larsen; Peder J. Pedersen (Institute for the Study of Labor (IZA), 2012)
The paper studies the impact from variations in unemployment on retirement among older workers. We integrate unemployment variations with early retirement programs and other pathways out of the labor force. The paper describes retirement programs, policy changes, labor force participation among older workers and presents a new estimate of the trend in the average age of retirement. Individual panel data for the last 25 years are used in estimations of the impact from individual unemployment on the retirement decision. Unemployment is found highly significant and quantitatively important for the retirement decision. We conclude that there is a clear risk of a cyclical downturn resulting in a more long run reduction in productive capacity with negative consequences for the budget of the public sector.
urn:nbn:de:101:1-201208175077
Keywords: E32; J21; J26; J64; 330; unemployment; labor force participation; retirement; Flexible Altersgrenze; Arbeitslosigkeit; Altersgrenze; Dänemark